PEMODELAN INFLOW PERFORMANCE RELATIONSHIP (IPR) TERHADAP PEMASANGAN INFLOW CONTROL DEVICE (ICD) PADA SUMUR PRODUKSI DARI RESERVOIR HETEROGEN MULTILAYER - Triyudha, Angga
One of the purpose of production technique is to optimize oil production rate. To get the optimum production rate, there are some obstacles that can lead to barrier, such as the difference of permeability and reservoir pressure at any layer. The difference of permeability and reservoir pressure at any layer cause the reduction of oil production rate in production well so that the optimum production rate can not be achieved. It can be solved by installing inflow control device (ICD). This study gives solution to the problem by doing simulation. This study uses model of black oil with solution gas drive reservoir. In the early stage, it is checked whether installing ICD will optimize the oil production rate in production well or not. Next, simulation is done to determine the location of ICD installation. ICD installation sensitivity is done at layer 1, layer 3, and layer 5. Next, the spesification ICD is determined. ICD spesification sensitivity is done with five variations of ICD, such as: ICD 3’:4 ½”:1.6, ICD 40’:6 5/8”:1.6, ICD 40’:5 ½”:3.2, ICD 40’: 4 ½”:0.8, dan ICD 40’: 4 ½”:3.2 where each number of parameters represent length of ICD, diameter of ICD, and rating of ICD. Last, the dimensionless IPR with ICD is generated with its application in the field. Simulation results show that the most optimum production rate in production well is obtained by installing the ICD in a layer that has the highest reservoir pressure (3460 psi) at depth of 11250 ft in layer 5. However, ICD spesifications have no significant effect to oil production rate. Dimensionless IPR equation is Qo/Qo,max=1-0.48(Pwf/Pr)-0.52(Pwf/Pr)2.